A Non-Randomized Controlled Trial of Prevention Guidance of Common Physiological Symptoms in Pregnancy for Self-Efficacy in Pregnant Women - Asih, Fransisca Retno; Danti, Renita Rizkya; Winarna, Nuristy Brillian Ainindyahsari (Universitas Aisyah Pringsewu, 2023)
Low self-efficiency causes twice the risk of experiencing discomfort due to pregnancy complaints. Providing prenatal education reduces it, but no studies using animated videos on the CPSP prevention guidance against self-efficacy were found. This study aimed to ascertain the impact of Common Pregnancy Symptoms in Pregnancy (CPSP) prevention guidance on pregnant women's self-efficacy. The design of this research is a non-randomized controlled trial in one of the independent health centres of midwifery in Banyuwangi, Indonesia. This study was conducted from July to September 2023 on 60 pregnant women with purposive sampling, so two groups of 30 were allocated to the control and experimental groups. After the intervention, a significant difference was observed in the average self-efficacy scores between the control and experimental groups (p = 0.000). Before and after the intervention, the average self-efficacy scores in the experimental group were 22.73±4.51 and 28.58±4.26, respectively, demonstrating a statistically significant difference (p = 0.000). This study encourages health professionals, midwives, and antenatal service providers to use the prevention guidance of CPSP in the first contact of antenatal care to remain relevant and timely with pregnancy information amid the administrative bustle.